Performance evaluation of monolith based immobilized acetylcholinesterase flow-through reactor for copper(II) determination with spectrophotometric detection - Parawee Rattanakit (2018)
A monolith based immobilized acetylcholinesterase (AChE) flow-through reactor has been developed for the determination of copper(II) using flow injection spectrophotometric system. The bioreactor was prepared inside a microcapillary column by in situ polymerization of butyl methacrylate, ethylene dimethacrylate, and 2,2-dimethoxy-1,2-diphynyletane-1-one in the presence of 1-decanol, followed by vinyl azlactone functionalization and AChE immobilization. The behavior of AChE before and after being immobilized on the monolith was evaluated by kinetic parameters from Lineweaver and Burk equation. The detection was based on measuring inhibition effect on the enzymatic activity of AChE by copper(II) using Ellman's reaction with spectrophotometric detection at 410 nm. The linear range of the calibration graph was obtained over the range of 0.02-3.00 mg L -1 . The detection limit, defined as 10% inhibition (I 10 ), was found to be 0.04 mg L -1 . The repeatability was 3.35 % (n=5) for 1.00 mg L -1 of copper(II). The proposed method was applied to the determination of copper(II) in natural water samples with sampling rate of 4 h -1 . © 2014 Parawee Rattanakit and Saisunee Liawruangrath.